2021
DOI: 10.1007/s40145-020-0434-1
|View full text |Cite
|
Sign up to set email alerts
|

IR-transparent MgO-Gd2O3 composite ceramics produced by self-propagating high-temperature synthesis and spark plasma sintering

Abstract: A glycine-nitrate self-propagating high-temperature synthesis (SHS) was developed to produce composite MgO-Gd2O3 nanopowders. The X-ray powder diffraction (XRD) analysis confirmed the SHS-product consists of cubic MgO and Gd2O3 phases with nanometer crystallite size and retains this structure after annealing at temperatures up to 1200 °C. Near full dense high IR-transparent composite ceramics were fabricated by spark plasma sintering (SPS) at 1140 °C and 60 MPa. The in-line transmittance of 1 mm thick MgO-Gd2O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…In addition, considering the problem of phase transformation from cBN to hBN due to its metastability during hightemperature and long-time sintering, it is crucial to choose suitable sintering technology and process parameters. SPS, a superior sintering technology to heat powder materials via a sequence of direct current pulses [19], possesses high heating rate, and short holding time [20], which can shorten the exposure time of the cBN grains at high temperatures and suppress phase transformation from cBN to hBN [18,21].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, considering the problem of phase transformation from cBN to hBN due to its metastability during hightemperature and long-time sintering, it is crucial to choose suitable sintering technology and process parameters. SPS, a superior sintering technology to heat powder materials via a sequence of direct current pulses [19], possesses high heating rate, and short holding time [20], which can shorten the exposure time of the cBN grains at high temperatures and suppress phase transformation from cBN to hBN [18,21].…”
Section: Introductionmentioning
confidence: 99%
“…Theoretically, this was because the Raman spectrum detects vibrations from nonpolar symmetric molecules [40,41], and the BP@MgO QD crystals are strongly polarized crystals with weak vibrations from symmetric molecules. In other words, different from MgO crystals [42,43], the lack of Raman signal just proved that the symmetry of the MgO QDs was broken, or even that it had no symmetry at all. In contrast, the FTIR spectrum showed ample information from polar molecules (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that the reduced grain size will increase the mechanical properties of ceramics. Spark plasma sintering (SPS) technique is an effective method to obtain nano-grained transparent ceramics due to the relatively low sintering temperatures and short sintering time [1,5,10,[27][28][29][30][31][32].…”
Section: Introduction mentioning
confidence: 99%